Cobalt-nickel supported on desilicated HZSM-5 for the conversion of Reutealis trisperma (blanco) airy shaw oil to liquid hydrocarbon products - Marlinda, Lenny; Rahmi; Aziz, Abdul; Roesyadi, Achmad; Hari Prajitno, Danawati; Al-Muttaqii, Muhammad; Mirzayanti, Yustia Wulandari (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
Desilication/alkaline treatment and metal impregnation were used to create the HZSM-5 catalyst supported by Co-Ni. These catalysts' isotherm patterns combined type I and type IV isotherms. This isotherm pattern showed a hysteresis loop at comparatively higher pressures. The pore size distribution of the mesoporous HZSM-5 catalysts was situated between 6 and 12 nm in size. Its use in the hydrocracking of Reutealis trisperma (Blanco) airy shaw oil (RTO) to produce biofuel was investigated. The results of the catalytic test showed that the hydrocarbon makeup of the biofuel was comparable to that of fuel. In comparison to HZSM-5, the mesoporous Co-Ni/HZSM-5 catalyst enhanced n-paraffin by 46.32 area% and aromatic by 34.18 area% in the hydrocracking of RTO.